2019
DOI: 10.5539/ies.v12n11p36
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Cyberbullying Behaviors of Sports College Students

Abstract: Studies conducted show that verbal and physical aggressive behaviors particularly among students are affected by the cyberbullying behaviors that are recently becoming even more prevalent with the increase in the social media tools. Such a case may also raise the need for investigating the cyberbullying behaviors of students of sports education in particular. Therefore, the aim of this study is to determine the cyberbullying behaviors of Sports College students. The sample of the study consists of 658 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Many studies have been conducted to investigate the phenomenon of CB in various contexts across the world (Alfandari, 2019;Antoniadou et al, 2016;Aricak, 2009;ARICAK et al, 2020;Ata & Adnan, 2016;Balakrishnan, 2015Balakrishnan, , 2018Bernardo et al, 2020;Bevilacqua et al, 2017;R. C. Forssell, 2020;Cáceres-Reche et al, 2019;Calvete et al, 2010;Dilmaç & Aydoǧan, 2009;Dogar, 2019;Ferreira et al, 2016;R. Forssell, 2016;Francisco et al, 2015;Jenaro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been conducted to investigate the phenomenon of CB in various contexts across the world (Alfandari, 2019;Antoniadou et al, 2016;Aricak, 2009;ARICAK et al, 2020;Ata & Adnan, 2016;Balakrishnan, 2015Balakrishnan, , 2018Bernardo et al, 2020;Bevilacqua et al, 2017;R. C. Forssell, 2020;Cáceres-Reche et al, 2019;Calvete et al, 2010;Dilmaç & Aydoǧan, 2009;Dogar, 2019;Ferreira et al, 2016;R. Forssell, 2016;Francisco et al, 2015;Jenaro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Dogar (2019) studied the behavior of CB among college students. The findings of his study revealed that there were statistically significant differences between sports college students' CB behaviors and their age, sex, parental educational status, means of following matches, frequency of watching matches, attendance at away matches, membership in sports associations, social media accounts, purposes, and levels of using such accounts.…”
Section: Introductionmentioning
confidence: 99%
“…çalışmalarında sporcuların antrenmanlarda, müsabaka öncesi ve sonrasında farklı zorbalık türlerine maruz kalabildiklerini belirlemiştir. Benzer şekilde dijital araçlar aracılığıyla şiddet biçimlerinin yaşanması mümkün olan sporda bireyler, farklı amaçlar ve farklı şekillerde şiddetin öznesi veya mağduru haline gelebilmektedir(Cantor, Joppa ve Angelone, 2020;Doğar, 2019;Meggs ve Ahmed, 2021;Oshiro, Weems ve Singer, 2021; Sanderson ve Weathers, 2019).Kavanagh, Jones ve Sheppard-Marks (2016)'ın elit düzeyde sporcuların dijital ortamda yaşadıkları deneyimleri konu edindikleri çalışmada sporcuların fiziksel, duygusal ve cinsel şiddete uğradıklarını ve etnisite, din, engellilik ve cinsel yönelim özelliklerden dolayı ayrımcı yaklaşımlarla kötü muameleye maruz kaldıklarını belirlemiştir.Teknolojik gelişmeler ve bu gelişmelerin ortaya çıkardığı yeni iletişim platformlarının geldiği aşama, dijital şiddetin güncel bir konu olarak kalmaya devam edeceğini göstermektedir.Yine gençlerin bu araçlarla sosyalleşmeleri şiddet biçimlerini dijital alanda ortaya çıkarma ihtimalini artırmaktadır. Bu anlamda çalışma spor bilimleri bölümlerinde okuyan öğrencilerin yaşadıkları dijital şiddetin boyutlarını ortaya çıkarmayı ve diğer bölümlerde okuyan gençler ile karşılaştırmayı amaçlamaktadır.…”
unclassified